Fauna parasitoide de Phyllonorycter spp. en plantaciones de manzano de Lleida - Bellostas, J.J.=700 1 Olivella, E.; Verdu, M.J.; Sarasua, M.J.; Avilla, J.
(Es, En)
ilus., 12 ref.
Keywords: GRACILLARIIDAE; PHYLLONORYCTER; INSECTA; PARASITOIDES; MANZANA; ESPAÑA